Livelihood sustainability assessment of coffee and cocoa producers in the Amazon region of Ecuador using household types - Viteri Salazar, Oswaldo (2018)
Supporting small farmer livelihoods in fragile, biodiverse regions, such as tropical forests, is a priority for manydevelopment agencies and national governments. These regions tend to be characterized by recent humansettlements, increasing populations and infrastructure development, as well as competitive land use activities,which exert pressure on fragile ecosystems. Improvement in livelihood strategies often focuses on increasingyields by improving productivity, but without taking into account alternative methods, such as better agri-cultural practices and their dependence on agrochemical inputs, changing land use through crop substitution, orimproving product commercialization. In this research, we use household types, defined according to differentland use patterns, in the Northern Amazon region of Ecuador to explore the limitations of, and identify futureoptions for, improving livelihood strategies based on small-scale coffee and cocoa production. The results of thedifferent types are discussed in order to highlight the methods' utility and identify benefits in terms of en-vironmental and social objectives versus economic profitability. Lessons are drawn that could be useful in ap-plications of public policy aimed at the betterment of small coffee grower and cocoa farmer livelihood strategies,which involve thousands of families in the Amazon region of Ecuador, without compromising the environment.